MEDICAL REFLECTION: THE URGENCY OF FASTING THERAPY - Asrofik, Asrofik; Umar, Aftah Wahab Ibnu; Nafiah, Siska Lailatul; Ridwan, Syafira Chairunnissa; Ishaq, Ala'; Waez, Abdurrahman; Amiruddin, Muhammad (International Journal of Multidisciplinary Reseach, 2025)
Fasting, traditionally defined as refraining from consuming food and drink for a set duration, has been acknowledged not only as a religious or cultural practice but also as a scientifically valuable approach to promoting health. In contemporary medicine, fasting has gained significant attention due to its influence on metabolism, the immune system, and hormonal balance. Research indicates that structured fasting can enhance cellular performance via autophagy, a biological process that eliminates damaged or unnecessary cellular components, contributing to the prevention of degenerative diseases. Metabolically, fasting proves effective in regulating blood sugar levels, lowering LDL cholesterol, and increasing insulin sensitivity, thereby offering promising prospects for the prevention and management of metabolic diseases. The role of fasting in modern healthcare extends beyond physical health benefits to include systemic regulation that helps prevent chronic conditions. However, the application of fasting protocols should be customized to individual needs, particularly for specific groups such as individuals with preexisting medical conditions, pregnant women, and children.